The Hospital Anxiety and Depression Scale: a pilot study to examine its latent structure and the link between psychological state and symptom severity in transient ischaemic attack patients. Issue 5 (3rd July 2016) - Spurgeon, Laura; James, Gill; Sackley, Cath
Abstract: Transient ischaemic attack (TIA) is often associated with anxiety and depression, which may precipitate secondary stroke and interfere with treatment. The Hospital Anxiety and Depression Scale (HADS) is widely used to assess these states and to inform the management of any associated psychological problems, but there is considerable debate about what it actually measures. The HADS scores from a range of different clinical groups have been reviewed in order to assess its psychometric properties, but so far, no research has examined either its latent structure when used with TIA patients, or the association between symptom severity and the test's validity. The aims of this study, therefore, were to investigate: (a) the underlying structure of the HADS when used with TIA patients; and (b) the impact of symptom severity on the validity of the HADS. The HADS and a functional capacity measure were administered by post to a sample of 542 confirmed TIA patients. Exploratory factor analysis was conducted on the HADS scores to establish its underlying structure for this clinical group, and then, sub-sample correlations were undertaken between the anxiety/depression scores for different levels of functional capacity. Two factors emerged, with 13 of the 14 HADS items loading significantly on both, suggesting there is a common affective state underlying the standard anxiety and depression scales. Further data-exploration indicated that convergence between these affective states increased as functional capacity deteriorated. The results suggest firstly that the HADS measures general subjective distress when used with TIA patients, and secondly that the higher reported symptom severity in this clinical group may be associated with reduced affective differentiation. As the ability to retain clear affective discrimination is associated with health and well-being, this could provide a focus for post-TIA rehabilitation.